2015
DOI: 10.1111/1467-8578.12107
|View full text |Cite
|
Sign up to set email alerts
|

Twins with autism: utilising video feedback to improve job‐related behaviours

Abstract: Employment for individuals with autism spectrum disorders (ASD) is a significant factor in assuring quality of life in adulthood. The research reported in this article examines the effectiveness of video feedback (VFB) in improving the job-related behaviours of twin adolescents with ASD and learning disabilities. The targeted behaviours included active engagement, decision-making, responding to others, hygiene, and transition making. A within-participant multiple-probe design across targeted job behaviours, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Fourteen studies used single-subject design to examine VBIs associated with the employment of youth with ASD, while five studies used a group design. Two studies combined VBIs with another intervention, such as a performance cue system , direct feedback from a job coach (Mackey & Nelson, 2015), literacy-based behavioral interventions (LBBI; Pistoro et al, 2018), and social skills curriculum (Walsh et al, 2018). Findings indicated that the majority of studies focused on teaching job performance skills associated with specific job duties, and only a few targeted the utility of VBIs to improve job search skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies used single-subject design to examine VBIs associated with the employment of youth with ASD, while five studies used a group design. Two studies combined VBIs with another intervention, such as a performance cue system , direct feedback from a job coach (Mackey & Nelson, 2015), literacy-based behavioral interventions (LBBI; Pistoro et al, 2018), and social skills curriculum (Walsh et al, 2018). Findings indicated that the majority of studies focused on teaching job performance skills associated with specific job duties, and only a few targeted the utility of VBIs to improve job search skills.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies had teachers or a job coach as the intervention agent (Cihak & Schrader, 2009;Gentry et al, 2015;Goh & Bambara, 2013;Mackey & Nelson, 2015;Walsh et al, 2018), while the rest were implemented by researchers. Five studies included family members (Burke et al, , 2013Van Laarhoven et al, 2012;Walsh et al, 2018) not to implement the VBI, but to complete social validity measurements or fidelity checks.…”
Section: Implementersmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Seven studies occurred in work-based learning or internship experiences in the community. 52,[54][55][56][57][58][59] One study entailed work-based learning in both community and school settings. 52 Two studies occurred in CIE contexts.…”
Section: Employment Contexts and Job Tasksmentioning
confidence: 99%
“…59 Autistic twins participating in work-based learning experiences learned employment-related social skills such as active engagement and responding to others. 58 Finally, one young adult employed in a retail store used VM to learn customer service phrases and interactions. 61…”
Section: Employment Contexts and Job Tasksmentioning
confidence: 99%